Reproducción de Bairdiella ronchus (Pisces: Sciaenidae) en la Ciénaga Grande de Santa Marta, Caribe Colombiano - Torres Castro, Liliana (1999)
FromFebruary 1993 through January 1994 a total of 890 irídividuals of Bairdielld roncus (Cuvíer) were captured in llie'Ciénaga Orande deSanta Marta (CGSM). Most were caught with casting nets,using the "corral